2017
DOI: 10.1007/s10803-017-3044-1
|View full text |Cite
|
Sign up to set email alerts
|

Developing Autism Screening Criteria for the Brief Infant Toddler Social Emotional Assessment (BITSEA)

Abstract: There is a critical need for evidence-based, broadband behavioral, and ASD screening measures for use in pediatric and early educational settings to ensure that young children at risk for developing social-emotional disorders and/or ASD are provided with early intervention services to optimize long-term outcomes. The BITSEA is a 42-item screener designed to identify social-emotional/behavioral problems and delays/deficits in social-emotional competence among 11-to-48-month-olds; 19 items describe behaviors con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 49 publications
(53 reference statements)
0
16
1
Order By: Relevance
“…The Brief Infant-Toddler Social Emotional Assessment was evaluated in a combined community low risk sample of 2 year old children (n=3127) and a clinical sample of preschool children with ASD; receiver operating curve analyses identified a subset of items (“autism score”) showed good discrimination of children with and without ASD. Clinical cut-off points were recently proposed on the basis of a case-control study but have yet to be evaluated in a prospective screening study 128. Other ASD screening tools have shown some promise, but initial data are limited to case-control comparisons (for example, Baby and Infant Screen for Children with aUtism Traits (BISCUIT)129; Quantitative Checklist for Autism in Toddlers (Q-CHAT)130131), high risk cohorts (for example, Autism Parent Screen for Infants (APSI)132), or modest community samples with small numbers of true positives requiring further study (for example, First Year Inventory (FYI)111133).…”
Section: Screening and Surveillancementioning
confidence: 99%
“…The Brief Infant-Toddler Social Emotional Assessment was evaluated in a combined community low risk sample of 2 year old children (n=3127) and a clinical sample of preschool children with ASD; receiver operating curve analyses identified a subset of items (“autism score”) showed good discrimination of children with and without ASD. Clinical cut-off points were recently proposed on the basis of a case-control study but have yet to be evaluated in a prospective screening study 128. Other ASD screening tools have shown some promise, but initial data are limited to case-control comparisons (for example, Baby and Infant Screen for Children with aUtism Traits (BISCUIT)129; Quantitative Checklist for Autism in Toddlers (Q-CHAT)130131), high risk cohorts (for example, Autism Parent Screen for Infants (APSI)132), or modest community samples with small numbers of true positives requiring further study (for example, First Year Inventory (FYI)111133).…”
Section: Screening and Surveillancementioning
confidence: 99%
“…Furthermore, the BITSEA Autism score is continuing to undergo further research and revisions. The authors of the BITSEA recently examined preliminary cut-off scores for maximizing sensitivity and specificity with pre-existing ASD diagnoses (Kiss, Feldman, Sheldrick, & Carter, 2017). They demonstrated evidence of good preliminary sensitivity and adequate specificity, but found that lower specificity values related to language abilities, highlighting the need for continued research and possible adjustments to cut-off scores specifically for children with DD.…”
Section: Discussionmentioning
confidence: 99%
“…All participants were assessed on the cognitive scales of the Mullen Scales for Early Learning (MSEL; Mullen, 1995). Caregivers filled out a brief demographic questionnaire, as well as two autism screening tools: the Brief Infant Toddler Social Emotional Assessment (BITSEA; Briggs-Gowan, Carter, Irwin, Wachtel, & Cicchetti, 2004;Giserman Kiss, Feldman, Sheldrick, & Carter, 2017), and the Parent's Observation of Social Interaction (POSI; Smith, Sheldrick, & Perrin, 2013). They were also asked to report their child's comprehension of critical words in the study (cat, dog, and bed).…”
Section: Participantsmentioning
confidence: 99%